United Nations Primer for Development: Further Comment - Koo, Anthony Y. C. (Quarterly Journal of Economics, 1953)
United Nations Primer for Development: Further Comment Get access Anthony Y. C. Koo Anthony Y. C. Koo Michigan State College, Lansing Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 67, Issue 2, May 1953, Pages 275–280, https://doi.org/10.2307/1885338 Published: 01 May 1953